Comprehensive Analysis Of The Dynamics Of Physical Fitness Indicators Of Handball Players (Texas Journal of Multidisciplinary Studies, 2025)
This scientific study is dedicated to a comprehensive study of the main indicators that form the level of physical fitness of female handball players - speed, strength, endurance and agility. The study involved 24 athletes aged 17–20: 12 were divided into control (CG) and 12 into experimental (TG) groups. A specially developed physical training program was used for the experimental group. During the study, athletes' performance in the 30-meter dash, shot put, 4x10-meter relay, 1000-meter run, handstand pushups, and jumping were analyzed. The results showed that the athletes of the experimental group showed significant improvement in all indicators (p